Worms and war: A case report of trauma and tropical disease intersecting - Masumbuko Claude; Hawkes Michael (Wolters Kluwer Medknow Publications, 2010)
Background: We report a case of heavy intestinal infestation with Ascaris lumbricoides complicating the surgical management of a gunshot injury to the abdomen. Co-existent traumatic and infectious pathologies in this case highlight the complex burden of illness among children living in areas of violent conflict, with clinical relevance to trauma surgeons in the tropics.